2020
DOI: 10.1093/imrn/rnaa017
|View full text |Cite
|
Sign up to set email alerts
|

Abelian Groups Are Polynomially Stable

Abstract: In recent years, there has been a considerable amount of interest in stability of equations and their corresponding groups. Here, we initiate the systematic study of the quantitative aspect of this theory. We develop a novel method, inspired by the Ornstein-Weiss quasi-tiling technique, to prove that abelian groups are polynomially stable with respect to permutations, under the normalized Hamming metrics on the groups Sym(n). In particular, this means that there exists D ≥ 1 such that for A, B ∈ Sym(n), if AB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The proof uses the following proposition, which is a special case of Proposition A.3 of [5]. Proposition 3.2.…”
Section: The Non-p-stability Of Autmentioning
confidence: 99%
“…The proof uses the following proposition, which is a special case of Proposition A.3 of [5]. Proposition 3.2.…”
Section: The Non-p-stability Of Autmentioning
confidence: 99%
“…That is, different systems of equations may correspond to isomorphic groups. The starting point of the grouptheoretic approach to stability is the following observation from [6] (see also [11,Proposition 1.11]).…”
Section: Testability and Stability Of Systems Of Equationsmentioning
confidence: 99%
“…To express the more specific fact that XY = YX admits a family of testers coming from the Sample and Substitute algorithm, we say that XY = YX is stable (see Definition 1.5). A later work [11] improved upon the result of [6] by showing that we may take k(ε) = 1 ε O (1) , where the implied constant is absolute, and by providing a constructive proof.…”
Section: Introductionmentioning
confidence: 98%
“…The rate of stability is, roughly speaking, the dependence of ϵ and δ in Definition 2.2. See [2] for details. To make this precise we define the function D (S ,R) : R + → R + as follows:…”
Section: [6]mentioning
confidence: 99%
“…Mosheiff [2] showed that the rate of stability of Z d , d ≥ 2 is polynomial but not linear (with respect to symmetric groups with normalized Hamming distance) 1 .…”
Section: Introductionmentioning
confidence: 99%